Parental warmth predicts more child pro‐social behaviour in children with better emotion regulation. (24th June 2022) - Yavuz, H. Melis; Colasante, Tyler; Malti, Tina
Abstract: Parental warmth and child emotion regulation have each been implicated in the development of child pro‐social behaviours; however, their interactive benefits remain unclear. In this multi‐method, multi‐cohort longitudinal study, we examined the effect of parental warmth on child pro‐social behaviours at different levels of child emotion regulation. We collected data from 6‐ and 10‐year‐olds in Canada ( N T1  = 233; M age  = 8.41; SD  = 2.08) and their parents. Parental warmth, child emotion regulation, and child pro‐social behaviours were assessed via parent report. Children's baseline respiratory sinus arrhythmia (RSA; an indicator of cardiac regulatory capacity) was assessed as a correlate of emotion regulation. Child pro‐social behaviours were assessed concurrently and 1 year later. Results showed that higher parental warmth was related to higher concurrent prosocial behaviours and greater increases in prosocial behaviours over 1 year. These effects were strengthened for children with higher emotion regulation whether measured by parent report or RSA. We discuss implications for understanding pro‐social development in middle childhood from a strengths‐based perspective.